Pengaruh Harga dan Lokasi Terhadap Kepuasan Pelanggan Studi Kasus Pada Lembaga Kursus dan Pelatihan (LKP) Andini Jombang - Siti Isnaini (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2018)
Course and training institute Andini is one of many business that engaged in the field of beauty either for women or man. Not only giving a beauty care course and traing, but also wedding make up, which is interested by many people. Course and training institute Andini Jombang has an advantage than other Course and training institute. This study aim to know and explain the effect of price and location either partially or simultaneously to cosumer satisfaction. The sampling technique that is used in this study is non probability sampling, especially incidental sampling, with the accumulation of sample is 62 customer. The result of this study shows that: (1) price partially has a positive significant effect to consumer satisfaction, which thitung is 5,456 > ttabel (1,669), and the significant value is 0,000. (2) Location partially has a positive significant effect to consumer satisfaction, which thitung is 7,056 > ttabel (1,669), and the significant value is 0,009. (3) Price and location simultaneously have a positive significant effect to consumer satisfaction, which fhitung is 69,834 > ftabel (3,15), and the significant value is 0,000